KRAS Activation and over-expression of SIRT1/BCL6 Contributes to the Pathogenesis of Endometriosis and Progesterone Resistance - Jung-Yoon Yoo (Nature Portfolio, 2017)
Abstract Endometriosis is an inflammatory condition that is associated with progesterone resistance and cell proliferation, resulting in pain, infertility and pregnancy loss. We previously demonstrated phosphorylation of STAT3 in eutopic endometrium of infertile women with this disorder leading to over-expression of the oncogene BCL6 and stabilization of hypoxia-induced factor 1 alpha (HIF-1α). Here we report coordinated activation of KRAS and over-expression of Sirtuin 1 (SIRT1), a histone deacetylase and gene silencer, in the eutopic endometrium from women with endometriosis throughout the menstrual cycle. The mice with conditional activation of KRAS in the PGR positive cells reveal an increase of SIRT1 expression in the endometrium compared to control mice. The expression of progesterone receptor target genes including the Indian Hedgehog pathway genes are significantly down-regulated in the mutant mice. SIRT1 co-localizes with BCL6 in the nuclei of affected individuals and both proteins bind to and suppress the promoter of GLI1, a critical mediator of progesterone action in the Indian Hedgehog pathway, by ChIP analysis. In eutopic endometrium, GLI1 expression is reduced in women with endometriosis. Together, these data suggest that KRAS, SIRT1 and BCL6 are coordinately over-expressed in eutopic endometrium of women with endometriosis and likely participate in the pathogenesis of endometriosis.